Study of the Ribavirin drug adsorption on the surfaces of carbon nanotube and graphene nanosheet using density functional theory calculations. (15th September 2021) - Sheikhi, Masoome; Shahab, Siyamak; Balali, Ebrahim; Alnajjar, Radwan; Kaviani, Sadegh; Khancheuski, Maksim; Al Saud, Sultan
Abstract: Density functional theory (DFT) and time‐dependent density functional theory (TD‐DFT) calculations were performed in the solvent water for the study of the adsorption of the Ribavirin (RIB) on surfaces of the carbon nanotube (CNT) and graphene nanosheet (GNS). After the adsorption, the electronic properties of the CNT and GNS change. The adsorption energies are shown the strong adsorption in GNS/RIB (−0.816 eV) rather than CNT/RIB (0.544 eV). The dipole moment of CNT and GNS changes with the adsorption of the RIB from 0.00 to 4.57 and 7.05 Debye in CNT/RIB and GNS/RIB, respectively. The adsorption of the RIB molecule on CNT and GNS increases the value of λmax . The localized orbital locator and electron location function values for the CC bond confirm the stronger interaction between carbon atoms of GNS and RIB. Based on the results, it is suggested that GNS with a lower energy gap (3.03 eV) is a more suitable structure for adsorption of the RIB in comparison with the CNT (3.021). Abstract : The density functional theory (DFT) and time‐dependent density functional theory (TD‐DFT) calculations have been performed for studying the adsorption of the Ribavirin (RIB) on surfaces of the carbon nanotube (CNT) and graphene nanosheet (GNS) using the M062X/6‐31G* level of theory. Neutral bond orbital analysis displays a charge transfer process between the RIB drug and CNT and GNS nanostructures. The change in λmax was assessed by with investigation of calculated UV spectra. The localized orbital locator and electron location function values for the CC bond of the GNS/RIB complex confirm the stronger interaction between carbon atoms of GNS and RIB drug. Based on our calculations, it is suggested that GNS with a lower energy gap is a more suitable structure for adsorption of the RIB in comparison with the CNT. The results of our study can be used to design a suitable carrier of the drug for the RIB drug.